Hackathon as a testing ground for creating digital tools in domestic Oriental studies - Kudakaev R.F.; Mokretskiy A.Ch.; Kostyrkin A.V. (Восточная Азия: факты и аналитика)
With the formation of a new technological paradigm and global competition for leadership in the digital space, the attention of experts is shifting towards the growth of political, economic and R&D influence of Eastern countries, which imposes new demands on research methods and tools. The article summarizes the experience of enhancing the academic research process through involving young IT professionals in the Oriental studies in competitive mode. During two weeks of the “Hackathon” contest organized by Yandex Cloud, Napoleon IT and AI Talent Hub in collaboration with the experts from the Institute on Oriental Studies and the Institute of China and Contemporary Asia of the Russian Academy of Sciences, contestants were challenged to develop a chat bot employing generative models and machine translation to analyze news flows of East Asian countries, primarily China and Japan. A review of the winners’ approaches and solutions proves overall feasibility of the idea and shows that many specific linguistic and engineering tasks that were relevant only recently have already been successfully solved. Therefore, when planning and developing next-generation digital tools, it is necessary to operate at functionally and semantically higher levels of generalization closer to human reasoning.